Mengenal Dunia Digital Sejak Dini: Pelatihan Microsoft Word untuk Anak Sekolah Dasar - Muhammad Furqon; Lilis Suharti; Siti Komala; Leonita Maharani; Achdan Firjatullah; Durotun Nisah; Muhammad Sulton (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
In today’s digital era, early mastery of basic technology is essential. This community service program aimed to introduce Microsoft Word, a fundamental word-processing tool, to elementary school students in Cempaka Village. The training targeted 5th and 6th graders, most of whom had limited or no experience with computer applications. Using a hands-on, "learning by playing" approach, the program made digital learning accessible and engaging for children. The materials covered included an introduction to the Microsoft Word interface, basic operations such as typing, saving, and editing documents, as well as text formatting and image insertion. Results showed a significant improvement in the students’ basic skills and confidence in using Microsoft Word. Participants expressed enthusiasm and interest in continuing to practice their new abilities. This initiative represents a strategic first step in fostering digital literacy among rural children, helping them prepare for the demands of an increasingly technology-driven world. Moreover, it underscores the importance of early digital education as a foundational element for students’ academic and personal growth.